« Between the heaven and man came the cloud » : John Ruskin et la représentation des états de la matière dans Modern Painters - Lawrence Gasquet (Cahiers Victoriens et Edouardiens)
The works of John Ruskin attempt to define the beauty of nature, so that man may be able to recreate it, to reprocess it through art and then access truth. Whether in the spheres of painting, architecture, or geology, Ruskin strives to guide the reader’s perception, and the four elements remain at the core of his thinking. What could be acknowledged as the representation of the various possible « states of matter », to use Ruskin’s expression in The Seven Lamps of Architecture, raises various questions : « Among the countless analogies by which the nature and relations of the human soul are illustrated in the material creation, none are more striking than the impressions inseparably connected with the active and dormant states of matter. I have elsewhere endeavoured to show, that no inconsiderable part of the essential characters of beauty depended on the expression of vital energy in organic things, or on the subjection to such energy, of things naturally passive and powerless » (The Seven Lamps of Architecture, London, George Allen, 1880, 1906, p. 271). In this article, I shall try to establish a synthesis of the representations of the four elements so as to determine the role they play in Ruskin’s aesthetics.